Metastasis Patterns and Prognosis of Elderly Patients With Esophageal Adenocarcinoma in Stage IVB: A Population-Based Study - Qiu, Guanghao; Zhang, Hanlu; Wang, Fuqiang; Zheng, Yu; Wang, Zihao; Wang, Yun (Frontiers in Oncology, 2021)
Abstract Background: Esophageal Adenocarcinoma (EAC) is the most common kind of esophageal cancer. Age at diagnosis of advanced EAC is relatively older. The studies about the practice patterns for elderly EAC patients with distant metastasis (DM) are limited. This retrospective, population-based study, using data from the Surveillance, Epidemiology, and End Results (SEER) was conducted to evaluate 855 elderly EAC patients with DM from 2010 to 2015. Methods: 855 elderly EAC patients with DM between 2010 and 2015 were included in this study. Univariate and multivariate Cox-regression and Kaplan-Meier analysis were used to assess prognosis. According to the site of metastasis, patients were classified to bone-only, brain-only, lung-only, liver-only and multiple (patients with two or more organs metastasis) group. Overall survival (OS), cancer-specific survival (CSS), median survival time (MST) and survival rate (SR) were evaluated to analyze the survival outcomes. Results: The most common metastasis site was liver among the single organ metastasis population, followed by lung, bone and brain. Compared with Bone-only group, the multiple group was associated with worst OS (HR: 1.037, 95%CI: 0.811-1.327, p=0.770） and CSS (HR:1.052, 95%CI: 0.816-1.357, p=0.695). The multiple group also had the lowest MST in the population (MST: 2 months in OS and 3 months in CSS) and SR (6-month SR: 27.1% in OS, 29.9% in CSS, 1-year SR: 10.7% in OS, 12.0% in CSS, 3-year SR: 2.5% in OS, 2.8% in CSS). Conclusion: The treatment was an independent prognostic factor affecting CSS and OS. Chemotherapy played a vital role in prognosis. Elderly patients with multiple metastasis had the worst OS and CSS and elderly patients with bone-only metastasis had the worst OS and CSS among single organ metastasis population.